Frequency of spermatophore production and regeneration in the males of Tityus (Atreus) magnimanus Pocock, 1897 (Scorpiones, Buthidae) - LK Ross (Journal of Venomous Animals and Toxins including Tropical Diseases, 2009)
The frequency of spermatophore production and the amount of time between matings for laboratory-reared males of Tityus (Atreus) magnimanus to regenerate spermatophores were examined. Males attain sexual maturity at the fifth or sixth instar (after a period of 137 to 155 days) and can produce initial spermatophores shortly after maturation. After mating, males can regenerate spermatophores within a single 24-hour period and remate. The present contribution represents the first report on an aspect of reproductive biology in this species and is part of a continuing study of the life history and post-embryonic development of Tityus (Atreus) magnimanus.